Anti - Fungal Activity of Selected Medicinal Plants Against Collecto trichum gloeosporioides Causing Onion Leaf Twister disease (OLTD) - Geethangini, T.; Pakeerathan, K.; Mikunthan, G. (University of Jaffna, 2022)
Onion Leaf Twister disease (OLTD) is a catastrophic fungal disease of small onion caused by Colletotrichum gloeosporioides in the dry zone of Sri Lanka. OLTD is char¬acterized by twisted leaves with chlorosis, abnormal necks and elongated bulbs. Farm¬ers rely on fungicides to manage this seed born disease. Current Sri Lanka's Agricul¬tural policy bans the use of synthetic agrochemicals and promote the growers to organ¬ic cultivation of onion. Therefore, an investigation was carried out to find out a sustain¬able solution to manage OLTD using botanicals. Medicinal plants showing antifungal properties such as rhizome of Acorus calamus, leaves of Aegle marmelos, Ocimum ba¬cilicum, Ocimum sanctum, Ocimum tenuiflorum and Ricinus communis (wild) were selected and aqueous extracts of 10%, 20% and 30% were tested under laboratory con¬dition using poison food technique. The experimental setup was arranged in a CRD design. The data obtained were subjected to ANOVA using SAS 9.1 and DMRT test was administrated to identify the best treatment at P <0.05. The inhibition percentage was significantly lower in 10% and 20% concentration of all the botanicals treated trails than the 30% concentration. Highest inhibition percentage of 78.04±0.12 % was exhibited by A. calamus after 9th day of inoculation in 20% concentration extracts. Whereas prominent results were derived from 30% of A. calamus rhizome extracts by giving significantly best mycelial inhibition of 82.4 ±0.06% at 11th day of inoculation followed by leaves extract of A. marmelos (81.4±0.12%) and R. communis (79.1±0.43%). In conclusion, rhizome extracts of A. calamus could be an alternate rem¬edy to manage OLTD. Field studies are in progress for further confirmation of the in-vitro findings.
Keywords: Acorus calamus; Biorationals; Leaf Twister disease; Onion; Medicinal plants